Success Metrics of the Ridho Illahi Breeders' Cooperative in Enhancing Welfare in Wanasaba - Prima, Suci Rahmawati; Una Atsawan, Muhammad; Cahyadi, Ni Made Ayu Krisna; Ruron, Maria G. N Timu (Universitas Ahmad Dahlan, Yogyakarta, 2024)
This study aims to examine the factors that determine the success of breeder cooperatives, particularly in enhancing business competitiveness and the welfare of the breeder community. The research employs a descriptive-qualitative method with Interpretive Structural Modelling (ISM) analysis. Data were collected through interviews and focus group discussions (FGD) with members of the Ridho Illahi Breeders Cooperative in Wanasaba subdistrict, West Nusa Tenggara. The results indicate that several factors contribute to the success of breeder cooperatives, with the technical skills of breeders having the most significant impact. The ISM model highlights that the critical areas of focus for breeder cooperatives should be the operation of upstream and downstream business systems and the marketing strategies for livestock products. The contribution of this research provides valuable insights for breeder cooperative management to enhance business competitiveness. The originality of this study lies in its model used to identify key factors for the success of breeders in improving competitiveness and welfare.